THE IMPACT OF FINANCIAL INCLUSION STRATEGIES ON PERFORMANCE OF SAVING AND CREDIT COOPERATIVE ORGANISATIONS. - EDWIN WAMANI (UGANDA CHRISTIAN UNIVERSITY, 2024)
This study was primarily set to assess the impact of financial inclusion on performance of SACCOs. The study consisted of three objectives; to examine the impact of financial advice on performance of SACCOs, to examine the impact of affordable credits on performance of SACCOs, and to examine the impact of savings services on performance of SACCOs. The study was conducted at Hoima Central Market Sacco. Cross-sectional design was adopted as study design. Questionnaire was employed as data collection instrument. In addition, the study found that, financial inclusion has significant effect on performance of SACCOs.